FAKTORâFAKTOR PREDISPOSISI YANG MEMPENGARUHI PEMBENTUKAN TEMPERAMEN BAYI USIA 2 â 3 BULAN - Setyaningsih, Maria Magdalena; Widhia Purwandhani, Eli Lea (Journal Nursing Care and Biomolecular, 2018)
In infancy, temperament is a major influence on reaction and adaptation to a particular environment. Adaptable infants show positive reactions to the stimuli that they received. The aim of this research is to know the predisposing factors that influence the formation of baby temperament of 2-3 months. Methods the study used analytical research with a retrospective approach. Bivariate analysis using Pearson Moment Product Correlation, multivariate analysis using linear regression. The results obtained by Multiple R 0.512 express the degree of closeness of the relationship of predisposing factors to the temperament of infants aged 2-3 months, as well as a strong relationship between these predisposing factors with the baby temperament of 2-3 months of age. On the value of determination coefficient shows for 0.262 states the magnitude of the influence of these predisposing factors to the temperament of infants aged 2-3 months. This means that 26.2% of the diversity of baby temperaments aged 2-3 months is influenced by the presence of these predisposing factors. Therefore, in order to produce quality generation and able to adapt well to the environment, is very necessary formation of baby temperament since still fetus.